2018
DOI: 10.1111/eci.12913
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of axial spondyloarthritis: Consensus and controversies

Abstract: So, although the pathophysiology of axSpA remains incompletely understood, the progress in recent years in several fields of research in axSpA including genetics, diagnosis, imaging and therapeutics, hold great promise for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 35 publications
5
43
0
2
Order By: Relevance
“…Our results confirm these histological findings in the area of the vertebral bodies, as decreased GAG contents of morphologically unremarkable lumbar IVDs were observed in patients with r-axSpA. It was hypothesized that the development of syndesmophytes is preceded by cartilage loss [8]. These syndesmophytes are not only a mere sign of long-standing inflammation, but are the main cause of irreversible functional disability and independent from inflammation-related stiffness and pain [7].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results confirm these histological findings in the area of the vertebral bodies, as decreased GAG contents of morphologically unremarkable lumbar IVDs were observed in patients with r-axSpA. It was hypothesized that the development of syndesmophytes is preceded by cartilage loss [8]. These syndesmophytes are not only a mere sign of long-standing inflammation, but are the main cause of irreversible functional disability and independent from inflammation-related stiffness and pain [7].…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, new bone formation is a key feature of chronic stages of axSpA and contributes to the burden of the disease and functional disability beyond mere inflammation-related symptoms [7][8][9]. Earlier studies demonstrated that joint remodeling in patients with r-axSpA is characterized by incipient cartilage loss, subchondral infiltration of fibrous tissue, and later on eventual formation of new bone [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Extra articular involvement like recurrent uveitis, aortic regurgitation, inflammatory lesions of colon and ileocecal valve and IgA nephropathy are seen in some cases [6,7]. The exact mechanism of pathogenesis is unknown.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…Н.А. Семашко», Нижний Новгород, Россия; 7 ГУЗ «Областная клиническая больница», Саратов, Россия; 8 ГАУЗ КО «Кемеровская областная клиническая больница им. С.В.…”
unclassified
“…Тем не менее патогенез избыточной пролиферации костной ткани при СпА является очень сложным и до конца не изученным. Ключевая роль в развитии воспаления при АС отводится двум основным провоспалительным цитокинам: фактору некроза опухоли α (ФНОα) и интерлейкину 17 (ИЛ17), причем отмечена способность ИЛ17 потенцировать провоспалительный эффект ФНОα [8][9][10]. Имеются данные, демонстрирующие способность ИЛ17 не только поддерживать воспаление и вызывать повреждение тканей, включая остеорезорбцию, но и стимулировать избыточную остеопролиферацию при СпА за счет активации мезенхимальных стволовых клеток в области воспаленного энтезиса, дифференцировку остеобластов с последующим образованием синдесмофита (остеофита) [3,[10][11][12].…”
unclassified